Leisure and cultural identity: an empirical study based on root-seeking summer camp for ethnic Chinese new generation - Wang, Zhenhan; Ye, Sheling; Bei, Li (Frontiers in Psychology, 2024)
This study examines the role of root-seeking summer camps in enhancing Chinese cultural identity among the new ethnic Chinese generation (ECNG) amidst the challenges of globalization. Semi-structured interviews with thirty campers revealed that ECNG often lack clear ethnic consciousness, experience conflict in community relationships, and have limited opportunities for traditional cultural experiences. The study found that summer camps exert both intrinsic and extrinsic influences on campers. Intrinsically, they facilitate the internalization of leisure motivation, foster a deepened leisure experience, and promote strengthened leisure interactions. Extrinsically, they provide opportunities for leisure education and cultural immersion. Through this synergy, summer camps enhance the cultural identification of ECNG. However, the study also noted that course enjoyment and teaching staff behavior could influence perceptions of the camp. This study contributes to understanding the relationship between leisure and identity, explaining how summer camp activities enhance ECNG’s cultural identity, and offering insights for governments and agencies.